Analysis of Clinical Epidemiological Characteristics of 15,967 Lung Cancer Surgery Patients in Yunnan Cancer Hospital from 2013 to 2022 - Ruke TANG; Yujie LEI; Lianhua YE; Guangqiang ZHAO; Xudong XIANG; Gaofeng LI; Guangjian LI; Xi WANG; Ying CHEN; Kaiyun YANG; Xiaobo CHEN; Jiapeng YANG; et al. (Chinese Journal of Lung Cancer)
Background and objective Lung cancer is a disease with a high incidence rate in Yunnan province, yet there is a paucity of large-scale studies on its clinical epidemiology. This research aims to investigate the epidemiological characteristics of patients who underwent lung cancer surgery at Yunnan Cancer Hospital over the past decade, thereby providing a theoretical basis for the prevention and treatment of lung cancer. Methods Clinical data were collected from 15,967 patients who underwent lung cancer surgery at Yunnan Cancer Hospital between 2013 and 2022. A statistical analysis was conducted on the patients' general data, surgical information, pathological types of lung cancer, and other clinical epidemiological characteristics. Results Among the 15,967 cases of lung cancer, 46.3% were male and 53.7% were female, with the male-to-female ratio ranging from 0.68 to 1.61:1. The median age was 56 years (interquartile range: 49-63), and 37.0% of the patients were in the age group of 50-59 years. Since 2017, there has been an annual increase in the proportion of patients under the age of 60 years. The smoking status of the patients showed that 28.1% were smokers and 71.9% were non-smokers. Qujing city accounted for 41.4% and Kunming city for 23.2% of the cases in Yunnan province, with 29.6% of patients originating from Xuanwei and Fuyuan areas of Qujing city. The distribution of affected lung lobes was as follows: right upper lobe 28.2%, right middle lobe 6.3%, right lower lobe 20.1%, left upper lobe 22.7%, and left lower lobe 16.4%. The use of thoracoscopic surgery increased from 30.8% to 96.3%, with single-port thoracoscopic surgery comprising 61.3%. Lobectomy was performed in 64.2% of cases, wedge resection in 17.2%, and segmentectomy in 12.2%. The proportion of lobectomy decreased from 83.1% to 46.1%. The proportion of patients in stages 0-I increased from 43.5% to 82.8%, while stages II-IV decreased from 56.5% to 17.2%. Adenocarcinoma increased from 75.6% to 88.3%, and squamous cell carcinoma decreased from 21.5% to 8.6%. Among adenocarcinoma patients, 60.9% were female. Among sguamous cell carcinoma patients, 90.6% were male. The peak age for adenocarcinoma was 50-59 years, and for squamous cell carcinoma, it was 60-69 years. The smoking rate was higher among squamous cell carcinoma patients (65.9%) compared to adenocarcinoma patients (22.3%). Adenocarcinoma patients had a higher proportion in stages 0-I (76.3%), while squamous cell carcinoma patients were more prevalent in stages II-III (64.1%). Conclusion The findings indicate an increasing proportion of female patients with adenocarcinoma, a younger age of onset, a higher proportion of non-smoking lung cancer patients, and an increased proportion of stages 0-I lung cancer. These trends may reflect the epidemiological characteristics of patients undergoing lung cancer surgery in Yunnan and surrounding areas over the past decade.